PENGARUH LABA PER SAHAM, NILAI BUKU EKUITAS DAN ARUS KAS OPERASI TERHADAP HARGA SAHAM - Puspita, Yumna; samin, Samin (EQUITY, 2017)
This study was conducted to examine the effect of variable Earning Per Share, Book Value of Equity, and Cash Flow of Operation on the Stock Price in manufacture sector listed on the Indonesia Stock Exchange (IDX) during the period 2012-2014. The data obtained in this study were published financial statements. The population in this study amounted to 44 companies and 132 samples obtained from 44 companies during the 3 years of observation. Techniques in sampling using purposive sampling method. The analysis technique used is multiple linear regression to examine the effect between dependent and independent variables and hypothesis testing using the simultan test and parsial test with a confidence level of 5%. The results showed that simultaneous Earning Per Share, Book Value of Equity, and Cash Flow of Operation have a significant effect on the Stock Price. While the partial test results showed that Earning Per Share, book value of Equity and Cash Flow of Operation have significant effect on the Stock Price.